A submillimeter study of the IR dust bubble S 21 and its environs - Cappa, Cristina Elisabeth (2017)
Based on the molecular emission in the 12CO(2-1) and 13CO(2-1) lines, and on the continuum emission in the MIR and FIR towards the S 21 IR dust bubble, we analyze the physical characteristics of the gas and dust linked to the nebula and the presence of young stellar objects (YSOs) in its environs. The line emission reveals a clumpy molecular shell, 1.4 pc in radius, encircling S 21. The total molecular mass in the shell amounts to 2900 M⊙ and the original ambient density, 2.1 ×10 3 cm − 3 , indicating that the bubble is evolving in a high density interstellar medium. The image at 24 µm shows warm dust inside the bubble, while the emission in the range 250 to 870 µm reveals cold dust in its outskirts, coincident with the molecular gas. The detection of radio continuum emission indicates that the bubble is a compact Hii region. A search for YSOs using photometric criteria allowed to identify many candidates projected onto the molecular clumps. We analize if the collect and collapse process has triggered a new generation of stars.